STATE REGULATION OF PUBLISHING: PROSPECTS FOR DEVELOPMENT - Yuriy Safonov; Andrey Shtangret; Alexander Melnikov (Baltic Journal of Economic Studies, 2022)
The experience of most countries confirms that the development of modern information technologies does not reduce people's interest in books. The demand for publishing products remains stable, and in the context of the dynamic development of the digital economy and the priority of information as a resource for sustainable development, it is even growing. Thus, in the EU countries, 6 to 8 books are published per capita per year. In Ukraine, there are significantly different trends, because in 2020 the annual circulation of books in Ukraine amounted to 20.2 million copies, that is, 0.48 copies of books and brochures per one inhabitant of Ukraine. Under such conditions, the development of publishing entities requires strategic and conceptual organizational and financial support from the state in the context of more efficient use of limited financial resources. Since 2005, Ukraine has been implementing the "Ukrainian Book" program, which along with providing tax benefits to publishers and book distributors is a form of state support for publishing. The results of the audit of the effectiveness of the use of funds proved that the effectiveness of the use of state budget funds is not high enough, in particular due to the imperfection of the criteria for selecting publications. Based on the results of the study, a list of such criteria was formed. The methodological principles of expert evaluation of book publications declared by the subject of publishing business in accordance with the established criteria for the selection of book products using points have been formed. An evaluation scale based on the selection criteria was developed. Additional characteristics that specify the main criteria for selecting publications included in the program and financed from the budget are proposed. The number of the expert group (7-15 persons) is substantiated, which ensures the reliability of the examination. The developed methodological and practical principles are intended to partially solve the existing problems by establishing scientifically based criteria for more efficient use of state budget funds and satisfying the reading interest of Ukrainian citizens.